2014
DOI: 10.15832/tbd.25721
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of a Greenhouse Fan-Pad Cooling System: Gradients of Horizontal Temperature and Relative Humidity

Abstract: An experimental study is conducted to determine the performance parameters of system, as well as gradients of temperature and humidity along greenhouse when opening Fan-Pad cooling system. Measurements in the study were carried out by using seven sensors for different locations, as well as portable instruments. For this purpose, the five digital temperature and humidity sensors and two pyranometers were used during experiments. Among them, two were located outside greenhouse for external measurements. The rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In order to analyse the efficiency of the fan-pad systems, two distinct models were developed with fan and pad evaporative cooling systems [117], with the results showing the greenhouse efficacy could be increased through the use of such systems. When opening the fan-pad cooling systems, the relative humidity changes along with the greenhouses, from the pad panels to the exhaust fans, shows uniformity, but the temperature changes were usually non-uniform [118], which has to be considered while employing such mechanical systems within the greenhouses. The employed system in this study reduced the GH temperature from 30-33 • C to the range of 20-27 • C, and increased the humidity rate of 30-47% to 50-68%, where the outside climate conditions were 32 • C and 25% humidity.…”
Section: Evaporative Cooling Systemsmentioning
confidence: 99%
“…In order to analyse the efficiency of the fan-pad systems, two distinct models were developed with fan and pad evaporative cooling systems [117], with the results showing the greenhouse efficacy could be increased through the use of such systems. When opening the fan-pad cooling systems, the relative humidity changes along with the greenhouses, from the pad panels to the exhaust fans, shows uniformity, but the temperature changes were usually non-uniform [118], which has to be considered while employing such mechanical systems within the greenhouses. The employed system in this study reduced the GH temperature from 30-33 • C to the range of 20-27 • C, and increased the humidity rate of 30-47% to 50-68%, where the outside climate conditions were 32 • C and 25% humidity.…”
Section: Evaporative Cooling Systemsmentioning
confidence: 99%
“…Extreme temperatures inside the greenhouse will limit the plant growth, as well as its quality (Dayioğlu, Silleli 2015). Greenhouse crops must not be kept for long time at temperatures higher than 30 °C in case of tropical and subtropical flora (Bailey 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, studies of different control strategies indicated that smart management of natural ventilation for manipulating the environment under specific exterior conditions is an effective approach to improve productivity and increase benefits [124] . A smart tropical greenhouse that operates on solar panels and benefits from an adaptive design and covering materials (i.e., mesh screens) will maximize the use of natural and mechanical ventilation [144,[159][160][161][162] and will be less dependent on higher-cost cooling methods such as evaporative [67,[163][164][165][166][167] and high pressure fogging systems [168] . Nevertheless, the use of anti-insect screens decreases the natural ventilation capacity and aggravates thermal conditions.…”
Section: Energy Analysis and Optimization Modelsmentioning
confidence: 99%